2015
DOI: 10.2147/rrfu.s55831
|View full text |Cite
|
Sign up to set email alerts
|

High-intensity focused ultrasound for noninvasive body contouring: current perspectives

Abstract: Noninvasive devices for fat reduction have become increasingly popular over the past decade. High-intensity focused ultrasound (HIFU), already in use for nearly half a century for the noninvasive treatment of tumors, has only recently been evaluated as a method for the selective ablation of adipose tissue. HIFU works by focusing high-intensity ultrasonic waves at the level of the subcutaneous adipose tissue, causing focal coagulative necrosis with contraction and thickening of adjacent collagen bundles while s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Due to its consistency and accuracy, Barton and colleagues argued that ultrasound should be the gold standard for clinical subcutaneous adipose tissue thickness measurement. [13][14][15][16] All ultrasound measurements were done by the same evaluator to improve consistency. Ultrasound images showed that on average subjects went from 4.06 cm adipose tissue thickness at baseline to 2.77 cm at 4-month follow-up visit resulting in a 1.29 cm (31.9%) reduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its consistency and accuracy, Barton and colleagues argued that ultrasound should be the gold standard for clinical subcutaneous adipose tissue thickness measurement. [13][14][15][16] All ultrasound measurements were done by the same evaluator to improve consistency. Ultrasound images showed that on average subjects went from 4.06 cm adipose tissue thickness at baseline to 2.77 cm at 4-month follow-up visit resulting in a 1.29 cm (31.9%) reduction.…”
Section: Discussionmentioning
confidence: 99%
“…This study utilized ultrasound to detect changes in subcutaneous adipose thickness at baseline and follow‐up visits. Due to its consistency and accuracy, Barton and colleagues argued that ultrasound should be the gold standard for clinical subcutaneous adipose tissue thickness measurement 13–16 . All ultrasound measurements were done by the same evaluator to improve consistency.…”
Section: Discussionmentioning
confidence: 99%
“…electromagnetic technology, non-thermal pulsed focused ultrasound (pFUS) and lasers. 5,11,12 This two-center study investigated the safety and efficacy of a single 1060 nm diode laser treatment for the non-invasive reduction of flank fat.…”
Section: Immediate Effects and Adverse Eventsmentioning
confidence: 99%
“…Today many procedures have been developed for this purpose including surgery, cryolipolysis, lasers, radiofrequency (RF), high-intensity focused ultrasound, and medical approaches. [3][4][5][6][7] Although surgery is still the first choice with regard to the results obtained, the market trend is increasingly moving towards minimally or noninvasive procedures. 1 Among the panorama of new technologies, recently microwaves (MWs) has shown a promising role in body sculpting [8][9][10] improving the abdominal aspect, reducing the subcutaneous adipose tissue while preserving and/or improving skin tightening, through a noninvasive system, avoiding side effects and the necessity to extended patient's recovery time.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, aesthetic improvement in the abdomen appearance is not always achieved through a healthy lifestyle. Today many procedures have been developed for this purpose including surgery, cryolipolysis, lasers, radiofrequency (RF), high‐intensity focused ultrasound, and medical approaches 3–7 . Although surgery is still the first choice with regard to the results obtained, the market trend is increasingly moving towards minimally or noninvasive procedures 1 …”
Section: Introductionmentioning
confidence: 99%